Esophageal squamous cell carcinoma presenting as submucosal lesion with repeatedly negative endoscopic biopsies - Choudhary, Narendra S.; Bansal, Rinkesh K.; Puri, Rajesh; Guleria, Mridula; Sud, Randhir (Journal of Digestive Endoscopy, 2016)
A 74-year-old male presented with dysphagia for 2 months. Computed tomography revealed irregular wall thickening of the esophagus at T3 to T5 level. He underwent gastroscopy which revealed a submucosal bulge with normal mucosa at 25 cm from incisors. Repeated biopsies were taken, all were negative for malignancy. The patient underwent endoscopic ultrasound, and fine-needle aspiration was taken which was suggestive for squamous cell carcinoma.
Keywords: Dysphagia; endoscopic ultrasound fine-needle aspiration; squamous cell carcinoma